Antioxidant Properties of the Vam3 Derivative of Resveratrol - Seyedmohammad Ahmadi; Tiziana Marino; Mario Prejanò; Nino Russo; Marirosa Toscano (Molecules, 2018)
A considerable number of studies has shown that many constituents of foods derived from plants are effective and safe antioxidants. This explains the growing interest in natural antioxidants in food applications. The goal of this investigation was to evaluate the antioxidant properties of the Vam3, a resveratrol derivative, firstly isolated from ethanol extracts of Vitis amurensis Rupr as a secondary product, and to carry out a comparison with resveratrol and other phenolic compounds which are currently in the limelight all over the world due to their beneficial effects on the human body. The potential of Vam3 as an antioxidant was determined through the evaluation of some key thermodynamic parameters which are commonly used for this purpose and describe the antioxidant activity quite well. Various mechanisms through which antioxidants usually can carry out their action were also explored both in water and in apolar environment. The results indicated that Vam3 is an excellent candidate as a natural antioxidant.